Music Composition Learning Using Digital Audio Workstations in Higher Education: A Scoping Review - Uci Rahmawati; Rita Milyartini; Juju Masunah (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Negeri Jakarta, 2026)
This study aims to map research trends, pedagogical strategies, learning practices, outcomes, and challenges in music composition learning using Digital Audio Workstations (DAWs) in higher education. A scoping review approach was employed using the Population, Concept, and Context (PCC) framework and the PRISMA-ScR guidelines. Literature searches were conducted through Scopus, ERIC, DOAJ, Google Scholar, and supplementary manual searches for publications from 2015 to 2025. After the screening and eligibility process, 15 publications were included in the final analysis. The findings show that DAW-based composition learning in higher education is commonly implemented through practice-based, project/studio-based, self-directed, and hybrid learning models, including DAW-live coding practices. DAWs are positioned not only as production tools but also as creative learning environments that support ideation, exploration, revision, collaboration, and digital music production. Reported learning outcomes include increased learning independence, production competence, creative exploration, and awareness of the composition process. However, the review also identifies several challenges, particularly the limited use of systematic assessment indicators, uneven digital literacy, and institutional readiness related to facilities and learning resources. This study contributes to the literature by clarifying how DAWs function as pedagogical media in higher music education and by highlighting the need for more structured assessment rubrics and sustainable learning designs.